Anti-herpes simplex virus and anti-human cell growth activity of E-5-propenyl-2'-deoxyuridine and the concept of selective protection in antivirus chemotherapy. - Cheng, Y C (1980)
E-5-Propenyl-2'-deoxyuridine (E-5-propenyl-dUrd) inhibited the growth of herpes simplex virus (HSV) types 1 (HSV-1) and 2 in culture. The concentration of drug required to give a 2-log reduction in virus titer was 5 microM for HSV-1 and 23 microM for HSV-2. The anti-HSV-1 activity of this agent was more potent than 5-propyl-dUrd, equivalent to E-5(3,3,3-trifluoropropenyl)-dUrd, and less potent than E-5-bromovinyl-dUrd. The HSV-1 mutant (B2006) lacking the ability to induce virus-specific thymidine kinase could not be inhibited by E-5-propenyl-dUrd. The binding constants of E-5-propenyl-dUrd to HSV-1, HSV-2, varicella-zoster virus, and human mitochondrial thymidine kinases were established to be 0.2, 6.2, 0.3, and 0.8 microM, respectively. Thymidine phosphorylation catalyzed by human cytosol thymidine kinase could not be inhibited by E-5-propenyl-dUrd at a concentration 10-fold higher than the thymidine in the assay. When thymidine and E-5-propenyl-dUrd were added concomitantly at equal concentrations to virus-infected cells, the antiviral activity was not reversed in HSV-1 and only partially reversed in HSV-2. E-5-Propenyl-dUrd also inhibited the growth of human cells in culture with 50% inhibitory dose of 50 microM. Since this inhibition could be readily reversed by a lower concentration of thymidine, the idea of selective protection is proposed. This approach could avoid the cytotoxic effect of an antiviral agent with properties similar to E-5-propenyl-dUrd without sacrificing antiviral activity.